Elemente ale modului și stilului de viață a populației vîrstnice sub impactul tranziției la economia de piață în România - Gheorghe, Camelia; Puwak, Hildegard; Stanciu, Mariana (Calitatea Vieții, 1992)
One of the most afflicted social category in the transition period is that of the old-aged people. The paper underlines the causes of this unfavourness and some possible measures which must be taken in order to protect them.